Evidence-Based Practice in Education - Thomas, Gary; Pring, Richard (Open University Press, 2004)
The movement to evidence-based practice in education is as important as it is controversial, and this book explores the arguments of leading advocates and critics.The book begins with an explication of evidence-based practice. Some of the ideas of its proponents are discussed, including the Campbell Collaboration, and the application to education of Cochrane-style reviews and meta-analyses.The thinking behind evidence based practice has been the subject of much criticism, particularly in education, and this criticism is aired in the second part of the book. Questions have been raised about what we mean by evidence, about how particular kinds of evidence may be privileged over other kinds of evidence, about the transferability of research findings to practice, and about the consequences of a move to evidence-based practice for governance in education.Given that the origins of the interest in evidence-based practice come largely from its use in medicine, questions arise about the validity of the transposition, and contributors to the third part of the book address this transposition.
Keywords: méthodes de recherche; politique éducative; utilisation des recherches